The Effect of Various Penetration Enhancers on the Octyl Methoxycinnamate Permeability: Mechanisms of Action Study: Penetration enhancers o n OMC permeability - salimi, Anayatollah; Moghimipour, Eskandar; Kogani, Payam; Soleymani, Saeed Mohammad (Iranian Journal of Pharmaceutical Sciences, 2020)
Octyl methoxycinnamate is one of the ingredients in sunscreen products. The main aim of this study was to investigate the effect of different enhancers of in vitro skin permeability of Octyl methoxycinnamate. Octyl methoxycinnamate permeability parameters were evaluated through the whole skin of the rat with and without chemical enhancers including eucalyptus oil, urea, menthol and olive oil by Franz cell diffusion. The effects of enhancers on skin structure were also studied using DSC and FT-IR techniques. The skin prevented the permeability of Octyl methoxycinnamate so that after 24 hours less than 3% of the substance passed through the skin. The results of this study showed that by increasing the time, it is possible to increase the skin permeation and the highest rate of skin absorption were corresponded to olive oil (ERflux=63.074), eucalyptus oil (ERflux=48.78) and menthol (ERflux=33.5), respectively while the least amount of skin absorption was related to urea (ERflux=29.53). Chemical penetration enhancers are substances that interfere with the complex structure of the skin and protein lipids. Two endothermic transitions were obtained at about 67 (Tm1) and 112 ° C (Tm2) in thermogram of the hydrated whole rat skin. Tm1 and Tm2 seems to be due to the melting of the lipids and the irreversible intracellular keratin or melting of the lipid-protein (keratin) complex, respectively. The amount of Tm1, ΔH1 and ΔH2 were decreased by all penetration enhancers compared to the hydrated skin. The FT-IR results suggested the mechanism of increasing absorption effect by lipid fluidization and lipid extraction. All of penetration enhancers used in this study significantly increased the skin permeability of Octyl Methoxycinnamate.